Analysis of willingness for relocation of the local communities living in the Critical Tiger Habitat of the Sariska Tiger Reserve, India. Issue 11 (1st November 2016) - Jain, Purva; Sajjad, Haroon
ABSTRACT: Many Indian Protected Areas (PAs) act as a support system for the communities living in and around them. Large-scale human interventions in these PAs have resulted in biodiversity loss, threat to wildlife and habitat fragmentation. The Sariska Tiger Reserve (STR) is no exception. In this reserve, tiger ( Panthera tigris ) became extinct in 2004.To create inviolate space for the reintroduced tigers, government has planned voluntary relocation of villages located inside Critical Tiger Habitat. The voluntary relocation plan will be more challenging if people are not willing to get relocated from PAs. Therefore, we have empirically analysed the identified factors influencing local communities' willingness in getting relocated outside the STR using logit model. Results revealed that "restriction of access" and "market access" are the most influential factors and positively associated while forest dependency is negatively associated with local communities' willingness. Based on these results, it was recommended that policy should be directed towards restriction on accessing forest resources along with reduction in forest dependency by nurturing and strengthening villagers' livelihood to ensure successful relocation. Displacement of existed small markets around the reserve will also persuade them to relocate in areas more connected to market and other facilities.